Propriedade urbana e racionalidade capitalista: do assenhoreamento ao crescimento citadino de Passo Fundo entre 1800 e 1950 - Baccin, Diego José (2020)
This study seeks to identify and understand the model of land appropriation that was applied in the north of the state of Rio Grande do Sul. It is based, for this purpose, on a serial documentary investigation that makes it possible to analyze the process of occupation, possession and seizing of land in Passo Fundo, which legitimized the formation of private city property and its urbanization process between the 19th and 20th centuries, from the takeover of the region by militia captain Manoel José das Neves, approximately in 1827/1828, to the organization of the city's first urban master plan, in the 1950s. In view of the phenomenon of the mastery of spaces in the formation of the regional territory, one understands the dynamics of the social, economic, political, cultural and legal conditions, from which it took effect and it effectively organized the squatters, establishing the domains that became legitimate urban private property. In addition, it can be seen that the urban occupation and urbanization processes are permeated by a concept of modernization of the urban land structure, especially in Passo Fundo, related to the issue of municipal land that constituted the city's forera property. This modernizing perspective is part of a situation of development of a capitalist rationality in the increase of a civilizing force in favor of municipal urban growth that gave rise to distinct relations with the lands, in particular those administered by the Intendance and later by the City Hall, questioned and claimed by Mitra Diocesana. These relationships have been experienced over the course of more than a century, a period in which disputes for the possession legitimacy of municipal forera property intensified, especially in a conflict established between Mitra Diocesana and the municipal public administration, which arrogated to themselves the rights over these urban tracts. The analysis and understanding of the foreira property, in the context of city growth in Passo Fundo, allow a more faithful look at the process of regional land ownership carried out in the 19th century and about city growth in the urban context of the first decades of the 20th century. All of this was carried out based on the expectation of regional development, aimed at under the paradigmatic aegis of a capitalist rationality in line with civilizing principles aspired by local elites